Elektronic Traffic Law Enforcement (ETLE) sebagai Alat Rekayasa Sosial Terhadap Ketertiban Lalu Lintas - Fitriana, Alvi Lailatuz Zahro; Rayodin, Habib; Pakih, Ilham (Media Hukum Indonesia (MHI), 2024)
This study aims to describe Electronic Traffic Law Enforcement (ETLE) as a Social Engineering Tool for Traffic Order. The existence of traffic violations is evidence that social behavior needs to be regulated by binding laws and regulations to achieve social welfare and order. This research method uses a normative juridical research type, using a statute approach and data collection techniques using literature studies. The results of the study indicate that the existence of law as a social engineering tool to deal with changes in society that will continue to occur in accordance with the progress of the times, the authorities have issued new regulations to enforce traffic order by issuing digitalization of the ticketing process (ETLE).